Socio-economic conditions and small business vulnerability to climate change impacts in Hong Kong. (26th November 2019) - Lo, Alex Y; Liu, Shuwen; Cheung, Lewis T.O.
ABSTRACT: Small and micro businesses bear the brunt of climate change impacts in the climate-challenged economy. Vulnerability is embedded into the socio-economic trajectories of their primary decision-makers. Multiple vulnerabilities may arise if the decision-makers' socio-economic conditions are associated with climate-sensitive business characteristics. Previous research has provided little evidence on such linkages, thus losing insights into how different facets of vulnerability interact and evolve over time. This paper explores the interactions between elements of small business vulnerability and the socio-economic characteristics of their primary decision-makers. It draws on the results of a survey involving 116 owner-managers of small and micro businesses and in-depth interviews with a sub-sample. Study areas are three remote coastal communities in Hong Kong exposed to high floods. Results show that such interactions exist in multiple, non-linear ways. Socio-economic disadvantages (i.e. low education attainment, old age, low income, and female) are related to some aspects of small business vulnerability, while playing a role in mitigating or avoiding other aspects of it. The findings call for building frameworks that account for the multiple spheres in which vulnerabilities are engendered and their interactions, while allowing for complexities and feedback mechanisms.